GAMBARAN STRATIFIKASI SOSIAL DALAM CERITA PENDEK THE SLEEPING BEAUTY IN THE WOOD KARYA CHARLES PERRAULT - SINGKARA, FRANCHOYNESTTU EFRANA SALLOMO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Short story is a piece of prose fiction. Short story features a small cast of named characters, and focuses on a "single effect" or mood which can lead to the next event and storyline. In doing so, short stories make use of plot, resonance, and other dynamic components to a far greater degree than is typical of an anecdote, yet to a far lesser degree than a novel. While the short story is largely distinct from the novel. The Sleeping Beauty in the Wood is one of the famous short story written by Charles Perrault, a famous French writer and important person on his time, depict the social condition on his time where the social stratification happened in the society. This research entitled â€œGambaran Stratifikasi Sosial dalam Cerita Pendek The Sleeping Beauty in the Wood Karya Charles Perraultâ€ is created to give explanation about the social stratification that Charles Perrault depict in the short story The Sleeping Beauty in the Wood by using the sociological aspects such as status and honor and intrinsic aspects which mainly focused on expressions, dialogues, and actions through the interaction among the characters. The objectives of this research are to identify and analyze the social stratification depicted by Charles Perrault in The Sleeping Beauty in the Woods. To identify and analyze the short story, the writer uses sociological approach and social theory from Talcott Parsons about social stratification. The Sleeping Beauty in the Wood shows the status of the characters affect the honor influence to the others or otherwise, the honor effect the status of the characters through the dialogues, actions, and expressions which found in the interaction among the characters as the depiction of social stratification. ______________________________________________________________________________ Keywords: short story, social stratification, status, honor, expression, dialogues, actions, expression, the Sleeping Beauty in the Wood.